Utilization, Yield, and Accuracy of the FilmArray Meningitis/Encephalitis Panel with Diagnostic Stewardship and Testing Algorithm - Broadhurst, M. Jana (J Clin Microbiol, 2020)
The impact of diagnostic stewardship and testing algorithms on the utilization and performance of the FilmArray meningitis/encephalitis (ME) panel has received limited investigation. We performed a retrospective single-center cohort study assessing all individuals with suspected ME between February 2017 and April 2019 for whom the ME panel was ordered. Testing was restricted to patients with cerebrospinal fluid (CSF) pleocytosis. Positive ME panel results were confirmed before reporting through correlation with direct staining (Gram and calcofluor white) and CSF cryptococcal antigen or by repeat ME panel testing. Outcomes included the ME panel test utilization rate, negative predictive value of nonpleocytic CSF samples, test yield and false-positivity rate, and time to appropriate deescalation of acyclovir. Restricting testing to pleocytic CSF samples reduced ME panel utilization by 42.7% (263 versus 459 tests performed) and increased the test yield by 61.8% (18.6% versus 11.5% positivity rate; P < 0.01) with the application of criteria. The negative predictive values of a normal CSF white blood cell (WBC) count for ME panel targets were 100% (195/195) for nonviral targets and 98.0% (192/196) overall. All pathogens detected in nonpleocytic CSF samples were herpesviruses. The application of a selective testing algorithm based on repeat testing of nonviral targets avoided 75% (3/4) of false-positive results without generating false-negative results. The introduction of the ME panel reduced the duration of acyclovir treatment from an average of 66 h (standard deviation [SD], 43 h) to 46 h (SD, 36 h) (P = 0.03). The implementation of the ME panel with restriction criteria and a selective testing algorithm for nonviral targets optimizes its utilization, yield, and accuracy.